Automatic non-destructive three-dimensional acoustic coring system for in situ detection of aquatic plant root under the water bottom. (May 2016) - Mizuno, Katsunori; Liu, Xiaofei; Katase, Fuyuki; Asada, Akira; Murakoshi, Makoto; Yagita, Yasunobu; Fujimoto, Yasufumi; Shimada, Tetsuo; Watanabe, Yoshiaki
Abstract: Digging is necessary to detect plant roots under the water bottom. However, such detection is affected by the transparency of water and the working skills of divers, usually requires considerable time for high-resolution sampling, and always damages the survey site. We developed a new automatic non-destructive acoustic measurement system that visualizes the space under the water bottom, and tested the system in the in situ detection of natural plant roots. The system mainly comprises a two-dimensional waterproof stage controlling unit and acoustic measurement unit. The stage unit was electrically controlled through a notebook personal computer, and the space under the water bottom was scanned in a two-dimensional plane with the stage unit moving in steps of 0.01 m (±0.0001 m). We confirmed a natural plant root with diameter of 0.025–0.030 m in the reconstructed three-dimensional acoustic image. The plant root was at a depth of about 0.54 m and the propagation speed of the wave between the bottom surface and plant root was estimated to be 1574 m/s. This measurement system for plant root detection will be useful for the non-destructive assessment of the status of the space under the water bottom.